A biodistribution study of Hemiscorpius lepturus scorpion venom and available polyclonal antivenom in rats - R Seyedian (Journal of Venomous Animals and Toxins including Tropical Diseases, 2012)
The purpose of the present study was to investigate the biodistribution profile of the venom of Hemiscorpius lepturus, the most dangerous scorpion in Iran. Blood and tissue samples were taken at various predetermined intervals during a 400-minute period for the venom and a 360-minute period for the antivenom in rats. The radio-iodination was carried out using the chloramine-T method. The results showed that the descending order of venom uptake was skin, kidneys and intestine, respectively. The descending order of polyclonal antivenom uptake was kidneys, intestine, heart and lungs. The calculated pharmacokinetic parameters of the venom were Telimination half-life = 521.5 ± 12.6 minutes; Vd/F (apparent volume of distribution) = 14.9 ± 3.3 mL; clearance (CL/F, apparent total clearance of the drug from plasma) 0.02 ± 0.005 mL/minute and for the antivenom Telimination half-life = 113.7 ± 7.4 minutes; Vd/F = 13 ± 1.2 mL and CL/F 0.08 ± 0.01 mL/minute. The pharmacokinetics profile comparison of the venom with that of the antivenom shows that serotherapy may be more effective if administered within 2-4 hours following envenomation by H. lepturus.